Brexit as a result of internal contradictions in the ECONOMY OF THE European Union - E. Smirnov (Вестник университета, 2016)
The European Union (EU) at the present stage tests the period of serious social and economic transformations. Further expansion of the EU goes to an aggravation of internal contradictions between member countries. A possible exit of Great Britain from the EU (Brexit) imposes serious restrictions for further development of economic integration, the present article is devoted to.